ANALISIS PENERAPAN AKAD WADIAH YAD DHAMMANAH PADA PRODUK TABUNGAN HAJI BERDASARKAN PSAK 101 DI BANK SYARIAH INDONESIA KCP KUNINGAN A.YANI - Viola Aulia Hidayat Saputri; Gina Sakinah (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the implementation of the Wadiah Yad Dhamanah contract on the Hajj Savings product at Bank Syariah Indonesia (BSI) KCP Kuningan A. Yani, based on PSAK 101 on the Presentation of Islamic Financial Statements. This research employs a descriptive approach using observation and interviews conducted during fieldwork. In practice, the author was directly involved in assisting prospective hajj pilgrims, particularly in the process of opening hajj savings accounts, completing registration forms, and handling the initial deposit for the Hajj Administration Cost (Biaya Penyelenggaraan Ibadah Haji or BPIH). The findings show that the implementation of the Wadiah Yad Dhamanah contract in BSI’s Hajj Savings product is in accordance with sharia principles and PSAK 101 recognition standards, where customers’ funds are recorded as deposits (liabilities) and not subject to profit-sharing. However, the bank may provide a voluntary bonus (hibah) as a token of appreciation for customer trust.